Iron De?ciency Anemia as a Risk Factor for First Febrile Seizures a Case Control Study - V. Ramgopal Rao; P. Anil Kumar (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Febrile seizures in children are a common problem. Iron deficiency anaemia is known, among other contributing factors, to be an aggravating factor in febrile seizures. Iron deficiency anaemia is a condition that can be avoided and managed. The study goal was to identify iron deficiency anaemia as a trigger factor for febrile seizures (FS). To determine the association between Iron Deficiency Anemia (IDA) and the first episode of febrile seizures (FFS). Subjects and Methods: Investigation like hemoglobin, blood indices (MCV, MCH), and serum iron and serum ferritin are done for detection of iron deficiency anaemia and their relationship with the first episode of febrile seizure was observed. Results: In our study comprising 50 cases and 50 controls, 58% (29) of cases were diagnosed as IDA with FS, 18% (9) of controls were diagnosed as IDA with Febrile Illness (FI). This suggests IDA as a risk factor for febrile seizures with a significant P value of <0.001. Among 50 cases 42% (21) cases have FS without IDA and among 50 controls 82% (41) controls have FI without IDA were present in the current study. Conclusion: IDA was more common in children with FS than in those with febrile illness (FI) disease alone. The result suggests that the IDA can be a contributing factor to the FFS. Screening of IDA of children with FFS should be regarded. Fever can worsen the negative effects of anaemia or iron deficiency on the brain, which can lead to seizures.